A Virtual Comparison of the eCLIPs Device and Conventional Flow-Diverters as Treatment for Cerebral Bifurcation Aneurysms - Peach, T. W. (Cardiovasc Eng Technol, 2019)
PURPOSE: Effective, consistent, and complication-free treatment of cerebral bifurcation aneurysms remains elusive despite a pressing need, with the majority of lesions presenting in such locations. Current treatment options focus either on aneurysm coil retention, supported by a stent-like device positioned in the parent vessel lumen, or intrasaccular devices that disrupt flow within the aneurysm dome. A third alternative, i.e., the use of conventional (intraluminal) flow-diverters to treat such bifurcation aneurysms raises the problem that at least one daughter vessel needs to be jailed in such a deployment. The eCLIPs is a stent-like device that offers the possibility of flow-diversion at the aneurysm neck, without the drawbacks of daughter vessel occlusion or those of intrasaccular deployment. METHODS: In this study the eCLIPs device was virtually deployed in five cerebral bifurcation aneurysms and compared with a conventional tubular flow-diverter device. Computational fluid dynamics (CFD) simulations of the aneurysm haemodynamic environment pre- and post-implantation were conducted, and focussed on metrics associated with successful aneurysm occlusion. Absolute and relative reductions in aneurysm inflow rate (Q) and time-averaged wall shear stress (TAWSS) were recorded. RESULTS: The eCLIPs device was found to perform in a similar qualitative fashion to tubular flow-diverters, with overall reduction of metrics being somewhat more modest however, when compared to such devices. Aneurysm inflow reduction and TAWSS reduction were typically 10–20% lower for the eCLIPs, when compared to a generic flow diverter (FD(BRAIDED)) similar to devices currently in clinical use. The eCLIPs was less effective at diffusing inflow jets and at reducing the overall velocity of the flow, when compared to these devices. This result is likely due to the larger device pore size in the eCLIPs. Notably, it was found that the eCLIPs provided approximately equal resistance to flow entering and exiting the aneurysm, which was not true for the FD(BRAIDED) device, where high-speed concentrations of outflow were seen at the aneurysm neck along with local TAWSS elevation. The clinical implications of such behaviour are not examined in detail here but could be significant. CONCLUSIONS: Our findings indicate that the eCLIPs device acts as a flow-diverter for bifurcation aneurysms, with somewhat diminished occlusion properties comparing to tubular flow diverters but without the jailing and diminished flow evident in a daughter vessel associated with use of conventional devices.